Comparison of UV‐mediated Advanced Oxidation. Issue 7 (1st July 2013) - Rosenfeldt, Erik; Boal, Andrew K.; Springer, James; Stanford, Benjamin; Rivera, Susan; Kashinkunti, Ramesh D.; Metz, Deborah H.
Abstract : Advanced oxidation processes (AOPs) are finding key treatment niches in several applications, including groundwater remediation, water reuse, seasonal taste and odor control, and organic contaminant oxidation. AOPs are incorporated into a water treatment process train when traditional methods for the removal of organics such as coagulation, filtration, chemical oxidation, or ultraviolet (UV) photolysis alone are insufficient to remove specific contaminants.